Formation and Reduction of Toxic Compounds Derived from the Maillard Reaction During the Thermal Processing of Different Food Matrices - Xiong, Ke; Li, Meng-meng; Chen, Yi-qiang; Hu, Yu-meng; Jin, Wen (Journal of food protection, 2024)
•AGEs, HAAs, AA, 5-HMF, and PAHs are toxic substances that are produced during the thermal processing of certain foods.•The hazards present in thermal processing are closely linked to the Maillard reaction.•The presence of ingredients and processing techniques in food can result in the creation of potential hazards.•Natural antioxidants, when combined with modern processing techniques, can effectively alleviate harm. Advanced glycation end products (AGEs), heterocyclic aromatic amines (HAAs), acrylamide (AA), 5-hydroxymethylfurfural (5-HMF), and polycyclic aromatic hydrocarbons (PAHs) are toxic substances that are produced in certain foods during thermal processing by using common high-temperature unit operations such as frying, baking, roasting, grill cooking, extrusion, among others. Understanding the formation pathways of these potential risk factors, which can cause cancer or contribute to the development of many chronic diseases in humans, is crucial for reducing their occurrence in thermally processed foods. During thermal processing, food rich in carbohydrates, proteins, and lipids undergoes a crucial Maillard reaction, leading to the production of highly active carbonyl compounds. These compounds then react with other substances to form harmful substances, which ultimately affect negatively the health of the human body. Although these toxic compounds differ in various forms of formation, they all partake in the common Maillard pathway. This review primarily summarizes the occurrence, formation pathways, and reduction measures of common toxic compounds during the thermal processing of food, based on independent studies for each specific contaminant in its corresponding food matrix. Finally, it provides several approaches for the simultaneous reduction of multiple toxic compounds.